Penguatan Digitalisasi Layanan Dokumen Kependudukan Melalui PLAVON Kabupaten Sidoarjo - Hariyoko, Yusuf (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2023)
Technological advances force every government to digitize its activities, especially in the aspect of public services. Public service is a matter that describes the government of a region. Population documents that must be owned by every community need to be properly provided by the local government. The Sidoarjo Regency Government strengthens population service by using a digital portal named Plavon. The Department of Population and Civil Registration of Sidoarjo Regency continues to innovate and develop the portal properly and is able to provide services. However, the adaptation process sometimes does not work properly due to a lack of understanding and outreach to the community about new service models. The research method used is descriptive qualitative, with data collection techniques carried out by observation, interviews, and documentation. Facilities and infrastructure can be used properly in providing services through the Plavon portal. Service timeliness can also work well. Ease of access runs satisfactorily and is easily understood by users.